(untitled) (Albayan Scientific Journal, 2023)
The agricultural sector cannot play its role in economic development without provide an appropriate investment. The investments are considered as one of the most important means of implementing agricultural development, which in turn helps to increase production capacity programs and then increases of each of the rates of capital formation and the proportion of the contribution of agricultural sector in GDP Therefore, the study aimed to identify the role of agricultural investments in the development of the Libyan agricultural sector by measuring its efficiency and assessing its relationship with the Libyan agricultural output and targeted investment In order to achieve its objectives, the study relied on methods of descriptive and quantitative analysis to analyze data on the subject of the study through the use of some mathematical and statistical methods. The data of the study was obtained from the Central Bank of Libya. The study reached several results, including: By measuring the efficiency of agricultural investment in Libya during the period 2000-2015, it was found that each of the agricultural investment rate, return on agricultural investment, the intensification factor the investmen multiplier were respectively (0.10, 7.12,2.06,1.77). during the average period of the study, which indicates the efficiency of agricultural investment in Libya. The average annual coefficient of settlement was 2.92 during the study period, and from this, it became evident that the settlement factor was greater than the correct one, indicating the inefficiency of agricultural investment in Libya. The agricultural production depends on the elements of production, namely (capital, labor) and that the possibility of substitution is available between these two elements to achieve a specific volume of production. Thus, the required growth rate for agricultural investment necessary to achieve the desired growth rate in Libyan agricultural production was obtained; it was estimated at %9.4. By applying the Harrod-Domar model on the agricultural sector to measure the impact of agricultural investments implemented on the growth rate in this sector, the average growth rate in the agricultural sector arising from agricultural investment in Libya was about 5.54, which means that to increase the rate of growth of the agricultural sector by 1%, the rate of agricultural investment must be increased by 5.54% in order to achieve growth in the agricultural sector and thus growth in the Libyan economy.